Structure-tailored superlattice Bi7Ti4NbO21: Coupling octahedral tilting and rotation induced high ferroelectric polarization for efficient piezo-photocatalytic CO2 reduction - Jingren Ni; Rufang Zhao; Chendi Shi; Yuanyuan Ji; Aize Hao; Aiting Xie; Hongjian Yu; Siew Kheng Boong; Hiang Kwee Lee; Chuanqiang Zhou; Jie Han (Advanced Powder Materials)
Intergrowth ferroelectric semiconductors with excellent spontaneous polarization field are highly promising piezo-photocatalytic candidate materials. In addition, developing structural design and revealing polarization enhancement in-depth mechanism are top priorities. Herein, we introduce the intergrowth ferroelectrics Bi7Ti4NbO21 thin-layer nanosheets for piezo-photocatalytic CO2 reduction. Density functional theory (DFT) calculations indicate that interlayer lattice mismatch leads to increased tilting and rotation angle of Ti/NbO6 octahedra on perovskite-like layers, serving as the main reason for increased polarization. Furthermore, the tilting and rotation angle of the interlayer octahedron further increase under stress, suggesting a stronger driving force generated to facilitate charge carrier separation efficiency. Meanwhile, Bi7Ti4NbO21 nanosheets provide abundant active sites to effectively adsorb CO2 and acquire sensitive stress response, thereby presenting synergistically advanced piezo-photocatalytic CO2 reduction activity with a high CO generation rate of 426.97 ​μmol ​g−1 ​h−1. Our work offers new perspectives and directions for initiating and investigating the mechanisms of high-performance intergrowth piezo-photocatalysts.